SEASONAL VARIATION IN COLLEMBOLAN DIVERSITY: A COMPARATIVE STUDY OF AGRICULTURAL AND FOREST ECOSYSTEMS IN WARANGAL DISTRICT, TELANGANA STATE, INDIA - Lakshmi Merugu, Esam Narayana, (Chelonian Research Foundation, 2024)
This study investigates the seasonal variation in Collembolan diversity within agricultural and forest ecosystems in Warangal District, Telangana State, India, emphasizing the impact of seasonal changes and land use practices on soil arthropod communities. The Shannon-Weiner Index was used to assess the diversity of Collembola species during Winter, Summer, and Monsoon seasons. Results indicate that both ecosystems exhibit the highest diversity in Winter, suggesting favorable conditions for Collembolan populations. However, the agricultural ecosystem shows a marked decline in diversity during Summer, attributed to extreme temperatures and intensive farming activities, which disrupt soil habitats. In contrast, the forest ecosystem maintains relatively stable diversity across seasons, with a gradual decline during the Monsoon season, likely due to the protective nature of the forest environment that buffers against environmental fluctuations. The Monsoon season prompts a partial recovery in Collembolan diversity in both ecosystems, though agricultural lands recover more slowly due to issues such as waterlogging and soil compaction. These findings are consistent with previous studies that highlight the resilience of forest ecosystems and the vulnerability of agricultural lands to seasonal extremes. The study underscores the importance of adopting sustainable agricultural practices to mitigate the adverse effects of seasonal variations on soil biodiversity, ensuring long-term ecosystem health and productivity. This research contributes to the broader understanding of how land use and seasonal dynamics influence soil arthropod diversity, offering valuable insights for the management of agro-ecosystems in semi-arid regions.